In vitro conversion of adult murine endothelial cells to hematopoietic stem cells. Issue 12 (December 2018) - Barcia Durán, José; Lis, Raphaël; Lu, Tyler; Rafii, Shahin
Abstract The ability to generate hematopoietic stem cells (HSCs) in vitro would have an immeasurable impact on many areas of clinical practice, including trauma, cancer, and congenital disease. In this protocol, we describe a stepwise approach that converts adult murine endothelial cells (ECs) to HSCs, termed 'reprogrammed ECs into hematopoietic stem and progenitor cells' (rEC-HSPCs). The conversion, which is achieved without cells transitioning through a pluripotent state, comprises three phases: induction, specification, and expansion. Adult ECs are first isolated fromRunx1 -IRES-GFP ; Rosa26-rtTa mice and maintained in culture under EC growth factor stimulation and Tgfβ inhibition. In the first (induction) phase of conversion (days 0–8), four transcription factors (TFs)—FosB, Gfi1, Runx1, andSpi1 (FGRS )—are expressed transiently, which results in endogenousRunx1 expression. During the second (specification) phase (days 8–20), endogenousRunx1 + FGRS -transduced ECs commit to a hematopoietic fate and no longer require exogenousFGRS expression. Finally, the vascular niche drives robust proliferation of rEC-HSPCs during the expansion phase (days 20–28). The resulting converted cells possess a transcriptomic signature and long-term self-renewal capacity indistinguishable from those of adult HSCs. In this protocol, we also describe functional in vitro and in vivo assays that can be used to demonstrate that rEC-HSPCs are competent for clonal engraftment and possess multi-lineage reconstitution potential, including antigen-dependent adaptive immune function. This approach thus provides a tractable strategy for interrogating the generation of engraftable hematopoietic cells, advancing the mechanistic understanding of hematopoietic development and HSC self-renewal. Adult endothelial cells from mice are reprogrammed to hematopoietic stem cells without transitioning through a pluripotent state. The protocol also describes in vitro and in vivo assays to confirm that the resulting cells function as expected.